2021
DOI: 10.1016/j.avsg.2021.03.016
|View full text |Cite
|
Sign up to set email alerts
|

Lower Extremity Intermittent Negative Pressure for Intermittent Claudication. Follow-Up after 24 Weeks of Treatment

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…17 In a follow-up study of 10 patients who were treated for 24 weeks, with INP, a mean increase in PWD and maximal walking distance (MWD) was found. 18 However, in both studies a proportion of the patients did not show an improvement in walking capacity. It may therefore be clinically relevant to find criteria that could select whom would benefit from INP-treatment, and to rather focus on other efforts to increase peripheral blood circulation in patients most likely not to benefit from INP-treatment.…”
Section: Introductionmentioning
confidence: 78%
“…17 In a follow-up study of 10 patients who were treated for 24 weeks, with INP, a mean increase in PWD and maximal walking distance (MWD) was found. 18 However, in both studies a proportion of the patients did not show an improvement in walking capacity. It may therefore be clinically relevant to find criteria that could select whom would benefit from INP-treatment, and to rather focus on other efforts to increase peripheral blood circulation in patients most likely not to benefit from INP-treatment.…”
Section: Introductionmentioning
confidence: 78%
“…There was however a consensus for the need to find the most appropriate patient group through further research involving more participants. An existing evidence base for FlowOx™ [ 51 53 , 55 , 56 ], along with observed benefits from patients were well regarded. As researchers, clinicians and medical educationalists, they felt it ethically appropriate to implement novel and evidence-based interventions into their clinics.…”
Section: Discussionmentioning
confidence: 99%
“…The positive effects of intermittent negative pressure have been described to be caused by an increased arteriovenous pressure gradient, shear rate, and blood flow fluctuations, leading to improved endothelial function [ 53 , 54 ]. Data published after this qualitative study was undertaken, has revealed improvements in pain-free walking distance after 12 weeks of intermittent negative pressure-treatment [ 55 ] and in a follow-up study of 24 weeks of intermittent negative pressure-treatment, both pain-free and maximum walking distance increased [ 56 ]. FlowOx™ is a CE marked medical device intended for use by patients with peripheral vascular disease.…”
Section: Introductionmentioning
confidence: 99%